2002
DOI: 10.1002/jlcr.574
|View full text |Cite
|
Sign up to set email alerts
|

Labelled compounds of interest as antitumour agents – VIII. Synthesis of 2H‐isotopomers of pentamethylmelamine and of a potential prodrug thereof

Abstract: Treatment of 2‐chloro‐4,6‐(dimethylamino)‐1,3,5‐triazine with trideuteromethylamine gave 4,6‐(dimethylamino)‐2‐trideuteromethyl‐1,3,5‐triazine, an isotopomer of the experimental anticancer agent pentamethylmelamine (PMM). Mitsunobu coupling with 1,2‐dimethyl‐3‐hydroxymethyl‐5‐methoxy‐indole‐4,7‐dione gave 1,2‐dimethyl‐3‐(N‐(4,6‐bis(dimethylamino)‐1,3,5‐triazin‐2‐yl)‐N‐trideuteromethylaminomethyl)‐5‐methoxyindole‐4,7‐dione. This conjugate is a potential reductively triggered prodrug of PMM. Copyright © 2002 Joh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It entered clinics in the 1970s for the treatment of ovarian carcinoma but difficulties were encountered, as it was insoluble in water and thus is difficult to formulate. However, it has recently been recognised as a second-line treatment for ovarian carcinoma [12][13][14][15][16][17][18][19][102][103][104] . Schoentjes et al [105] reported a patent of indole derivatives with general formula (I) in 2011 and reported its use for the treatment of cancers ( Figure 11).…”
Section: Reported Indoles As Anti-cancer Active Agentsmentioning
confidence: 99%
“…It entered clinics in the 1970s for the treatment of ovarian carcinoma but difficulties were encountered, as it was insoluble in water and thus is difficult to formulate. However, it has recently been recognised as a second-line treatment for ovarian carcinoma [12][13][14][15][16][17][18][19][102][103][104] . Schoentjes et al [105] reported a patent of indole derivatives with general formula (I) in 2011 and reported its use for the treatment of cancers ( Figure 11).…”
Section: Reported Indoles As Anti-cancer Active Agentsmentioning
confidence: 99%